Low Polymerase Activity Attributed to PA Drives the Acquisition of the PB2 E627K Mutation of H7N9 Avian Influenza Virus in Mammals - Libin Liang; Li Jiang; Junping Li; Qingqing Zhao; Jinguang Wang; Xijun He; Shanyu Huang; Qian Wang; Yuhui Zhao; Guangwen Wang; Nan Sun; Guohua Deng; et al. (mBio, 2019)
ABSTRACT Avian influenza viruses (AIVs) must acquire mammalian-adaptive mutations before they can efficiently replicate in and transmit among humans. The PB2 E627K mutation is known to play a prominent role in the mammalian adaptation of AIVs. The H7N9 AIVs that emerged in 2013 in China easily acquired the PB2 E627K mutation upon replication in humans. Here, we generate a series of reassortant or mutant H7N9 AIVs and test them in mice. We show that the low polymerase activity attributed to the viral PA protein is the intrinsic driving force behind the emergence of PB2 E627K during H7N9 AIV replication in mice. Four residues in the N-terminal region of PA are critical in mediating the PB2 E627K acquisition. Notably, due to the identity of viral PA protein, the polymerase activity and growth of H7N9 AIV are highly sensitive to changes in expression levels of human ANP32A protein. Furthermore, the impaired viral polymerase activity of H7N9 AIV caused by the depletion of ANP32A led to reduced virus replication in Anp32a−/− mice, abolishing the acquisition of the PB2 E627K mutation and instead driving the virus to acquire the alternative PB2 D701N mutation. Taken together, our findings show that the emergence of the PB2 E627K mutation of H7N9 AIV is driven by the intrinsic low polymerase activity conferred by the viral PA protein, which also involves the engagement of mammalian ANP32A. IMPORTANCE The emergence of the PB2 E627K substitution is critical in the mammalian adaptation and pathogenesis of AIV. H7N9 AIVs that emerged in 2013 possess a prominent ability in gaining the PB2 E627K mutation in humans. Here, we demonstrate that the acquisition of the H7N9 PB2 E627K mutation is driven by the low polymerase activity conferred by the viral PA protein in human cells, and four PA residues are collectively involved in this process. Notably, the H7N9 PA protein leads to significant dependence of viral polymerase function on human ANP32A protein, and Anp32a knockout abolishes PB2 E627K acquisition in mice. These findings reveal that viral PA and host ANP32A are crucial for the emergence of PB2 E627K during adaptation of H7N9 AIVs to humans.